Isabelo delos Reyes and early Philippine studies, 1884-1891 - Dizon, Lino (Journal of Philippine local history and heritage, 2017)
This paper surveys the prodigious engagement of Isabelo de los Reyes in nascent Philippine studies, entwined with his career as a journalist under Jose Felipe Del-Pan. Spawning seven years, it starts in 1884 with the beginnings of folklore in the Philippines and ends in 1891, on Del-Pan's death and Isabelo's involvement in other preoccupations that included the Propaganda Movement capped by his documented lengthy dispute with Wenceslao Retana, the Spanish journalist. Among his many interests in early Philippine studies, two have been highlighted: Isabelo's incipient roles in Philippine folklore and in historical investigation.